정책투자우선순위 도출을 위한 레저스포츠 선호도와 참여도 분석 - 김경식(Kyong-Sik Kim); 구경자(Kyong-Ja Koo); 진은희(Eun-Hee Jin) (한국콘텐츠학회 논문지, 9(11), 2009)
In this research, to identify the degree of preference and participation in leisure sports, over 19-year-old adults living in the capital region were collected as subjects, and among them, 250 persons were chosen by purposive sampling method. Using SPSSWIN 16.0, I analyzed the collected data by reliability analysis, paired sample t-test, PPA(preference performance analysis) method. The conclusion is the following. First, the first quadrant showed wind surfing, skins-cuba, water-ski, and yacht, and as a result of this, it is necessary to improve the degree of participation in this field, the second quadrant showed golf, racketball snow board, ski, fishing, and climbing, and these field need to specific attention to maintain continuous attention, for they have a great deal of attendance, the third quadrant, showed water sleigh, cart, balloon, sky-diving, orienteering, hang gliding, model plane, and survival game. As the degree of preference and participation in these sports is low, it is recommended that more effort should be made for these sports. Finally, in the forth quadrant, there are tracking, mountain bike, inline skates, rafting, and cycling. As it's the participation is high, while that of preference is low, it is important to maintain the policy of the participation in leisure sports. Sencondly, the degree of preference and participation in leisure sport activicties acording to socio demographic characteristics differentiate. 본 연구는 PPA를 이용한 레저스포츠 선호도와 참여도를 규명하기 위하여 2009년 수도권의 만 19세 이상 성인을 연구대상으로 설정한 다음, 유의표집법으로 250명을 표본추출 하였다. 수집된 자료는 SPSSWIN 16.0을 이용하여 신뢰도분석, 대응표본t검증, PPA 분석기법 등의 방법이 활용되었다. 결론은 다음과 같다. 첫째, 레저스포츠 선호도와 참여도는 차이가 있다. 1사분면인 '중점개선' 종목은 윈드서핑, 스킨스쿠버, 수상스키, 요트 등이며, 2사분면인 '노력지속' 종목은 골프, 라켓볼, 스노보드, 스키, 낚시, 등산 등이다. 3사분면인 '개선요망' 종목은 워터슬래드, 카트, 열기구, 스카이다이빙, 오리엔테어링, 행글라이딩, 모형비행기, 서바이벌게임 등이며, 4사분면인 '현상유지' 종목은 트레킹, 산악자전거, 인라인스케이트, 래프팅, 사이클링 등이다. 둘째, 사회인구통계학적 특성에 따라 레저스포츠 선호도와 참여도 중점개선 종목은 차이가 있다. 성별에 따라서는 여자 집단에서 요트 선호도와 참여도간의 차이가 크며, 연령에 따라서는 20대 연령층에서 윈드서핑, 스킨스쿠버, 수상스키, 요트 선호도와 참여도간의 차이가 크다. 학력에 따라서는 대졸이상 집단에서 윈드서핑 선호도와 참여도간의 차이가 크며, 직업에 따라서는 전문자유직 집단에서 윈드서핑, 스킨스쿠버, 요트 선호도와 참여도간의 차이가 컸다.